The Routledge handbook of Star Trek - Garcia-Siino, Leimar; Mittermeier, Sabrina; Rabitsch, Stefan 1983- (Routledge literature handbooks, 2022)
"The Routledge Handbook of Star Trek offers a synoptic overview of Star Trek, its history, its influence, and the scholarly response to the franchise, as well as possibilities for further study. This volume aims to bridge the fields of science fiction and (trans)media studies, bringing together the many ways in which Star Trek franchising, fandom, storytelling, politics, history, and society have been represented. Seeking to propel further scholarly engagement, this Handbook offers new critical insights into the vast range of Star Trek texts, narrative strategies, audience responses, and theoretical themes and issues. This compilation includes both established and emerging scholars to foster a spirit of communal, trans-generational growth in the field and to present diversity to a traditional realm of science fiction studies." (Buchrückseite)